INTRACOMPANY PRICING. - Stone, Williard E. (The Accounting Review, 1956)
Abstract An efficient intracompany pricing system should establish a price that: 1. Fosters a healthy interdepartmental competitive spirit. 2. Provides an adequate profit yard-stick for the measurement of departmental management. 3. Provides figures to top management for use in policy decisions to make or to subcontract. 4. In some cases minimizes federal income taxes. The four methods available are: (a) Price established by top management. (b) Cost, cost plus fixed percentage, and standard cost methods. (c) The retail price offered to the producing division's other customers. (d) Interdepartmental bargained price method. Ideally the standard cost method would appear to afford the best answer to the four basic requirements. Certainly a company already using standard costs would find little in the other available methods to warrant their use. In the absence of an adequate standard cost system, the bar-gained price method has much to recommend it particularly if a list price with class discounts is used to offset long and tedious negotiations.